Prevalence of Salmonella in dressed and cooked broiler meat of different grocery shops, hotels and restaurants in Gazipur and Dhaka city of Bangladesh - Haque, AKM Ziaul; Kabir, S M Lutful; Siddiqua, Ayesha; Hussain, AZM Iftikhar (Asian-Australasian Journal of Food Safety and Security, 2018)
The study was conducted to find out the prevalence of Salmonella in dressed and cooked broiler meat in different shops and restaurants in Gazipur and Dhaka city including the sanitary quality. A total of 80 samples of dressed boiler, 88 cooked samples from road side fast food shops and small hotels, and 104 cooked samples from recognized fast food shops and restaurants were subjected to bacteriological isolation and identification. Highest number of Salmonella spp. were 42.5% in road side shops and 16.25% found in super market for dressed meat. Thigh muscle was more prevalent to breast muscle in both market types for dressed muscle. A total of 31 thigh muscles were positive for road side shop and 23 for super market where 26 and 19 breast muscle were positive for road side shop and super market respectively. Among the cooked meat or fried chicken incidence of Salmonella spp. were 23.86% in road side shops and 11.54% found in recognized shops. In case of both market source thigh muscle was highly prevalent in comparison to breast muscle. For cooked meat, a total of 19 thigh muscles were positive for road side fast food shops and small hotels, and 12 for recognized fast food shops and restaurants where 15 and 8 breast muscle were positive for road side fast food shops and recognized fast food shops respectively. Our results highlighted the need of implementing strict hygiene and sanitation standards to reduce the incidence of Salmonella. The prevalence of Salmonella in poultry products can be reduced effectively by identifying and eliminating the sources and contamination sites during slaughter and processing of poultry. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 40-44